Now, the Taller Die Earlier: The Curse of Cancer - Sohn, Kitae (Oxford University Press, 2016)
© 2015 The Author 2015. Published by Oxford University Press on behalf of The Gerontological Society of America. All rights reserved.This study estimates the relationship between height and mortality. Individuals in the National Health Interview Survey 1986, a nationally representative U.S. sample, are linked to death certificate data until December 31, 2006. We analyze this relationship in 14,440 men and 16,390 women aged 25+. We employ the Cox proportional hazards model, controlling for birthday and education. An additional inch increase in height is related to a hazard ratio of death from all causes that is 2.2% higher for men and 2.5% higher for women. The findings are robust to changing survival distributions, and further analyses indicate that the figures are lower bounds. This relationship is mainly driven by the positive relationship between height and development of cancer. An additional inch increase in height is related to a hazard ratio of death from malignant neoplasms that is 7.1% higher for men and 5.7% higher for women. In contrast to the negative relationship between height and mortality in the past, this relationship is now positive. This demonstrates the success and accessibility of medical technology in treating patients with many acute and chronic diseases other than cancer.